"Freud, Male Homosexuality, and the Americans" Revisited: A Brief Contribution to the History of Psychoanalysis. Issue 2 (2nd April 2016) - Abelove, Henry
ABSTRACT: Henry Abelove summarizes the main arguments of "Freud, Male Homosexuality, and the Americans, " a paper he wrote in the early 1980s. He also says that in writing it he aimed chiefly to challenge American moralism, which then was, and still is, both destructive and immensely influential.